EXPERIMENTAL AND NUMERICAL STUDY OF WELDED CURVED PLATES - MR. JAIDEEP BUDGUDE; MR. GANESH WAGH (International Journal of Innovations in Engineering Research and Technology, 2021)
Welding is widely used in all the fabrication process for the development of structural component. An accurate and physically suitable curved fillet model is tobegiven as input for analysis of welding process. Flux core arc welding (FCAW) is an arcwelding process that that usescontinuousflux cored filler wire . Theflux is used as a welding protection from the atmosphere environment. Materials like CS and MS with varying thickness of 5,6,7 mm and overlapping angles starting with 30° and success dingwith minimum difference of 5° in consecutiveangle up to100° and tested using UTM machine . Metallurgicalwelded joints that are in service may be subjected to high stresses and different types of loads such as fatigue loads, tension loads compression loads and thus temperature and residual stress modeling is one of the complex processeswhich utilize the weld parameters and properties at higher temperature. Finite element analysis (FEA) has become a practical method of predicting stresses and deflection for loaded structures. In this study, finite element analysis software, ANSYS, is used for a parametric study for effect